(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As technology is growing fast, using technologies is also increasing because the previous technologies cannot support the new requirements. In this case, every company is trying to implement newly released technologies. As IPv4 was introduced, it has been used for a long time in networking. But now, the limitations of IPv4 are too much, such as address limitation, subnet-ting with complex structure, inefficient NAT employment. This is why IPv4 is not considered to be used anymore. Because of IPv4 problems, the IPv6 protocol is designed and developed to overcome IPv4 limitations. The efficiency of IPv6 is more in packet processing, and routing pro-vides a simple network configuration and improves the QoS by decreasing latency in the time of the data packet transformation. As IPv6 has many features and new supported services. With the emergence of IPv6, any enterprise companies are interested in implementing IPv6 in the enterprise network. An enterprise network includes protocols, virtual and physical networks that connect all systems and users on a LAN, and all applications in the cloud and data center. The main purpose of this research is to implement ipv6in the enterprise network. We used the latest version of the Cisco packet Tracer for simulation purposes. Cisco packet Trace can simulate necessary routing using EIGRPv6, OSPVv3, and RIPng and application layer protocols.